Therapeutic effects of adipose tissue-derived mesenchymal stem cells on ER stress in a murine model of metabolic dysfunction-associated steatohepatitis: an in vivo and in vitro study - Norihiko Ogawa; Akihiro Seki; Alessandro Nasti; Ho Yagi; Masatoshi Yamato; Hiiro Inui; Hiroki Nomura; Takuya Komura; Hidetoshi Nakagawa; Kouki Nio; Hajime Takatori; Tetsuro Shimakami; et al. (Stem Cell Research & Therapy)
Abstract Background Metabolic dysfunction-associated fatty liver disease (MAFLD) is an increasing concern due to lifestyle changes, with metabolic dysfunction-associated steatohepatitis (MASH) leading to progressive liver damage, cirrhosis, and increased morbidity. The role of endoplasmic reticulum (ER) stress, particularly the unfolded protein response (UPR) pathway, in MASH progression remains unclear. Adipose tissue-derived stem cells (ADSCs) have shown promise in regenerative therapy; however, their mechanism for alleviating MASH-induced liver damage is not fully understood. In this study, we aimed to investigate the therapeutic mechanism of ADSCs in MASH, focusing on their modulation of ER stress in hepatocytes. Methods C57BL/6J mice were fed either an atherogenic high-fat diet (AT + HF) or a high-fat diet (HFD-60) to induce MASH and simple steatosis (SS), respectively. Liver tissues were analyzed for gene expression, protein levels, and apoptotic markers using DNA microarray, quantitative PCR, western blotting, histological staining, and caspase activity assays. ADSCs were harvested, cultured, and treated to assess their effects on ER stress. In vitro experiments investigated palmitic acid-induced ER stress in hepatocytes and the effects of ADSCs on hepatic stellate cells and inflammatory markers. Results The PERK arm of the UPR pathway was significantly upregulated in MASH liver tissues compared to SS tissues, correlating with increased apoptosis. ADSC administration reduced PERK activation, decreased apoptotic marker expression, and ameliorated hepatic fibrosis. However, ADSCs did not directly attenuate palmitic acid-induced ER stress in hepatocytes in vitro. Instead, they modulated the hepatic microenvironment by reducing hepatic stellate cell activation and IL-17-associated inflammation, indirectly mitigating ER stress and hepatocyte apoptosis. Conclusions ADSCs alleviate MASH progression by modulating ER stress via immunomodulation rather than through directly rescuing hepatocytes. These findings highlight the potential of ADSCs as an immunomodulatory therapeutic strategy for MASH and support further investigation into their clinical application.